Improvement of Emulsifying Properties of Wheat Gluten Hydrolysate λ-Carrageenan Conjugates - Jin-Shui Wang; Mou-Ming Zhao; Xiao-Quan Yang; Yue-Ming Jiang (Food Technology and Biotechnology, 2006)
Gluten hydrolysate was prepared through limited enzymatic hydrolysis of wheat gluten resulting from the byproducts of wheat starch. The enzyme applied in the present study was Protamex. Response surface methodology was used to investigate the effects of pH, gluten hydrolysate (GHP)λ-carrageenan (C) ratio and reaction time on emulsifying properties of the GHP-C conjugate. The regression model for emulsion activity index (EAI) was significant at p=0.001, while reaction time had a significant effect on EAI of the conjugate with regression coefficient of 4.25. The interactions of pH and GHP/ C ratio, and GHP/C ratio and reaction time significantly affected the EAI of the conjugate. Both the emulsifying property and nitrogen solubility index (NSI) of GHP-C conjugate prepared under the optimal conditions increased more remarkably, compared to the control. The denaturation temperature of GHP-C conjugate obviously increased compared to wheat gluten. The addition of GHP-C conjugate had different effects on dough characteristics. Moreover, this conjugate can delay the increase in the bread crumb firmness during storage. It demonstrated that this conjugate couldimprove the dough characteristics and had anti-staling properties of bread.